PENGARUH PENDIDIKAN GIZI BERBASIS VIDEO DAN BOOKLET TERHADAP PENGETAHUAN ANEMIA PADA REMAJA PUTRI SMK TUNAS GRAFIKA INFORMATIKA TAHUN 2020 - Riana Thasya Paramitha, (2021)
Background: In Indonesia, adolescent girls are still a risk group for anemia with a prevalence of 32%. As a form of prevention and control of anemia in adolescent girls, this study provides nutrition education about anemia using video and booklet. Objective: To analyzed the effect of nutrition education about anemia using video and booklet on knowledge of adolescent girls at SMK Tunas Grafika Informatika. Methods: This study is a quasy experimental pre-post test group design with a sample of 39 students in the video group and 39 students in the booklet group selected by cluster random sampling. The research data collection was conducted online. Result: There was an effect of the use of nutrition education using video media (p = 0,000) and booklets (p = 0,000) on the respondents' knowledge. The average difference test in the two media groups shows that the mean on video media (20.33) is higher than the average on booklet media (17.51). Conclusion: There was an effect of nutrition education using video media and booklets on knowledge related to anemia for adolescent girls of SMK Tunas Grafika Informatika, but there is no significant difference between the used of video media and booklet media.